2015
DOI: 10.1542/peds.2015-1487
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Abuse in Children With Sentinel Injuries

Abstract: OBJECTIVE: Child physical abuse is commonly missed, putting abused children at risk for repeated injury and death. Several so-called sentinel injuries have been suggested to be associated with high rates of abuse, and to imply the need for routine testing for other, occult traumatic injuries. Our objective was to determine rates of abuse evaluation and diagnosis among children evaluated at leading children's hospitals with these putative sentinel injuries.METHODS: This is a retrospective secondary analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 41 publications
7
93
1
Order By: Relevance
“…These findings suggest that implicit biases of medical providers may contribute to disproportionately high rates of child abuse evaluation and reporting for poor or African-American families, and disproportionately high rates of missed abuse in affluent, or White families. (Jenny, Hymel, Ritzen, Reinert, & Hay, 1999; Lindberg et al, 2015; Wood et al, 2012a; Wood, French, Song, & Feudtner, 2015; Wood et al, 2010)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that implicit biases of medical providers may contribute to disproportionately high rates of child abuse evaluation and reporting for poor or African-American families, and disproportionately high rates of missed abuse in affluent, or White families. (Jenny, Hymel, Ritzen, Reinert, & Hay, 1999; Lindberg et al, 2015; Wood et al, 2012a; Wood, French, Song, & Feudtner, 2015; Wood et al, 2010)…”
Section: Discussionmentioning
confidence: 99%
“…(Block & Palusci, 2006) The new sub-specialty has also increased the funneling of cases of suspected maltreatment into referral centers, and has raised the possibility of establishing a more uniform standard of care to decrease the broad variability in medical care of maltreated children. (Lindberg, Beaty, Juarez-Colunga, Wood, & Runyan, 2015; Paine, Scribano, Localio, & Wood, 2016; Wood, Fakeye, et al, 2015; Wood et al, 2012a)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study of child protection specialist paediatricians, broad variability was found in the perceived likelihood of physical abuse (Lindberg et al ., ). Several clinical studies from the USA reported considerable variation in the diagnostic investigations used (including skeletal surveys, neuroimaging and blood investigations) and in the identification of child abuse, even after adjusting for individual patient characteristics (Harper et al ., ; Lindberg et al ., ; Wood et al ., ). Other studies examined physicians' attitudes and willingness to report child abuse and neglect (CAN).…”
Section: Introductionmentioning
confidence: 98%
“…Although cross-sectional and retrospective studies provide correlation or association with child abuse and neglect, they do not provide evidence on the cause and effect of abuse or other variables that may mediate the cause and effect. Risk factors associated with abuse include a caretaker’s history of child abuse, negative caretaker perceptions of their child, caretaker affect or behavioral problems including substance abuse, caretaker cognitive and affective deficits, housing instability, non-biological caregiver in the home, chaotic or volatile family situations (Douglas & Mohn, 2014; Duffy, Hughes, Asnes, & Leventhal, 2015; Lindberg, Beaty, Juarez-Colunga, Wood, & Runyan, 2015; Miyamoto et al, 2017; Wathen & MacMillan, 2013; Young et al, 2018). Protective factors that increase family strengths and reduce the likelihood of child abuse and neglect include supportive social networks, stable family relationships, nurturing parenting skills, parental employment and adequate housing (Kumpfer & Magalhães, 2018; Saul et al, 2014; Schofield, Lee, & Merrick, 2013; Stith et al, 2009; Swenson & Chaffin, 2006).…”
Section: Introductionmentioning
confidence: 99%